JNK 1 Regulates Dopamine Release in the Associative Striatum in MK801 Schizophrenia Model - Wattanalurdphada, Rada (My University, 2024)
Various genes on the JNK1 pathway have been implicated in schizophrenia through genetic association studies. However, the effect of JNK1 on dopamine release has not been studied, the underlying mechanism remains poorly understood. Work from our group has previously using mass spectroscopy and bioinformatics analysis of GWAS data, providing evidence to suggest JNK1 may regulate brain functions that are disturbed in psychiatric disorders. We had identified that NMDA receptor subunits were downregulated at the cell surface in mice lacking Jnk1, suggestive of a “NMDA hypofunction” model of psychosis. This combined with a battery of behavioural anomalies representing a schizophrenia-like phenotype, led to the hypothesis to be tested, i.e. that hypofunction of NMDARs of interneurons would lead to hyperstimulation of the corticolimbic pathway, resulting in hyperdopaminergic release in the nucleus accumbens, otherwise referred to as the dorsal striatum. This current study emphasises the role of JNK regulates dopamine release in associative striatum and in the control of schizophrenia-like behaviour in mice. By using Jnk1 knock-out mice and pharmacological inhibition of JNK pathway. This study aimed to investigate whether dopamine release was altered in the associative striatum in the MK801 schizophrenia mice model. We presently show that Jnk1 knockout mice exhibited mild but significant schizophrenia-like behaviour, as indicated by the range of behaviour test in an open-field and Y-maze shown showed that Jnk1-/- mice pronounced deficit in motor coordination and locomotion. Moreover, non-competitive NMDAr antagonists such as MK801 induced dopamine regulates in associative striatum which induced schizophrenia-like behaviour in mice. The intrinsic hyperactivity of Jnk1-/- mice, aligns with their reduced surface expression of NMDA receptor subunits, and a possible NMDAR hypofunction model. Furthermore, these findings highlight the JNK pathway as putative novel drug target against schizophrenia disorder. Further investigation would be needed to clarify the gene’s mechanistic involvement and its potential therapeutic implications, especially in disorders characterized by NMDA receptor dysfunction. As we progress ahead in this line of research, understanding such intricate molecular-behavioural relationships becomes essential in developing targeted therapeutic strategies for neuropsychiatric conditions.
Keywords: JNK1, DLIGHT, associative striatum, MK801 schizophrenia model, NMDA hypofunction